The radiative impact of Nordic anthropogenic black carbon. Issue 1 (1st December 2016) - Hienola, Anca I.; O'Donnell, Declan; Pietikäinen, Joni-Pekka; Svensson, Jonas; Lihavainen, Heikki; Virkkula, Aki; Korhonen, Hannele; Laaksonen, Ari
Abstract : This study presents an assessment of the impact of black carbon (BC) regional emissions of four Nordic countries (Denmark, Finland, Norway and Sweden – denoted henceforth as DFNS). The surface concentrations, radiative forcing and BC-in-snow forcing were calculated using ECHAM-HAMMOZ global aerosol-climate model and, where possible, evaluated with field observations. We found that the model is reproducing the BC surface concentrations for most of the measurement sites considered within 1–2 standard deviations, with only few exceptions. The radiative forcing (top of the atmosphere, short-wave, clear and total sky) of BC emitted in DFNS on regional (Nordic and Arctic area separately) and global levels was calculated by removing the anthropogenic emissions from DFNS. The total values for clear sky for the three regions are 16.2±1.4, 2.9±0.28 and 0.04±0.022 mW/m 2, respectively. The presence of clouds enhanced the BC radiative forcing. The forcing caused by BC deposited on snow is roughly equal to the direct radiative forcing of airborne BC (17.3±3.34 mW/m 2 over DFNS, 4.2±0.77 mW/m 2 over the Arctic and 0.042±0.012 mW/m 2 globally).